1996
DOI: 10.1016/0006-2952(96)00032-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects on transmethylation by high-dose 6-mercaptopurine and methotrexate infusions during consolidation treatment of acute lymphoblastic leukemia

Abstract: ']a r is e n R o n n e y A. De Ahreu,*f HenkJ. Blom* Jos P.M. Bokkerinkf andj. M. Frans Trijbels* ♦ L a b o r a t o r y o f P e d i a t r i c s , a n d t C e n t e r f o r P e d ia t r ic : O n c o l o g y S.E. N e t h e r l a n d s , U n i v e r s i t y H o s p i t a l S t . R a d b o u d , P.O. Box 9101» 6500 HB N ijm e g e n , T h e N e t h e r l a n d s A BSTRA CT. 6 -mercaptopurine (6MP) cytotoxicity is caused by thioguanine and methylthioinosine nucleo tides. Thiopurine méthylation occurs to a large exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…34) Although these reactions could be oxidized by either XO or AO, the diŠerence in metabolite proˆle between oral and intravenus administration indicates that AO may be the major enzyme in 8-hydroxylation. 16) In addition, the results obtained in the present study and a higher capability of AO to produce 8-hydroxy metabolites from guanine and purine analogs compared with XO, 10,23) provide more support for the involvment of AO in the matabolism of thioxanthine to thiouric acid as the major enzyme. This may be account for the results obtained by Keuzenkamp-Jansen et al 32) These authors indicated that co-administration of allopurinol and high dose 6-MP infusion to patients with non-Hodgkin lymphoma resulted in a relatively higher plasma levels of 6-MP, 6thioxanthine and methylpurine and a lower thiouric acid plasma level compared to those who did not receive allopurinol.…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations
“…34) Although these reactions could be oxidized by either XO or AO, the diŠerence in metabolite proˆle between oral and intravenus administration indicates that AO may be the major enzyme in 8-hydroxylation. 16) In addition, the results obtained in the present study and a higher capability of AO to produce 8-hydroxy metabolites from guanine and purine analogs compared with XO, 10,23) provide more support for the involvment of AO in the matabolism of thioxanthine to thiouric acid as the major enzyme. This may be account for the results obtained by Keuzenkamp-Jansen et al 32) These authors indicated that co-administration of allopurinol and high dose 6-MP infusion to patients with non-Hodgkin lymphoma resulted in a relatively higher plasma levels of 6-MP, 6thioxanthine and methylpurine and a lower thiouric acid plasma level compared to those who did not receive allopurinol.…”
Section: Discussionsupporting
confidence: 51%
“…According to some reports, 6-MP is converted to 6thiouric acid through 6-thioxanthine, 6,32) whereas, other authors have suggested that the oxidation intermediate is 8-hydroxy-6-mercaptopurine. 1,9,10,17) The reason for this contraversy could be due in part to the diŠerence in metabolite proˆle between oral and intravenous administration of the drug. 16,33) It is more likely that following oral administration, 6-MP is predominantely oxidized to 6-thiouric acid via 6-thioxanthine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is found that the 6-MP plasma concentrations are unexpectedly low and highly variable with marked individual differences. By using standardized treatment regimens for some patients, the drug is difficult to keep in an optimal plasma level [5][6][7]. As a result, the use of a universal ''target dose" based on weight is not optimal and the determination of 6-MP over time becomes very important.…”
Section: Introductionmentioning
confidence: 99%